A Comparative Study of the Elements of Social Oppression and Pessimism in "Dawood Guz Pusht" and "Notre Dame de Paris - Dr. Muhammad Safeer; Dr. Aamir Zaheer; Dr. Robina Yasmin (Zaban-o-Adab, 2022)
This article is a comparative study of two literary works; “Dawood Guz Pusht” written in Persian language by an Iranian fiction writer named Sadiq Hidayat and a French novel titled “Notre Dame de Paris” by a famous French writer Victor Hugo. In these two literary works, we found a hunch-back as the main character which is victim of social oppression, contempt, hatred, inhuman behavior, and ruthless society. This paper is an attempt to present a comparative overview of the main characters in these two literary works; Quasimodo in French and Dawood Guz Pusht in Persian. The paper also emphasizes the influence of French literature on Persian, which is most profound in the twentieth century. The beginning of modern literature in Iran was generally considered to be the Constitutional Revolution (1905) or precisely the period when Iranian literature, due to the influence and fusion of western literature and culture, moved away from the traditional style and adapted to the new world. Thus, new genres namely novels, short stories, plays and poems, appeared around 1921. The departure of Iranian students to study in France and the establishment of Madrassa Dar al-Fanoon at Tehran are the main reasons of French influence in Iran.